Thorough Static Analysis of Device Drivers - Ball, Thomas; Bounimova, Ella; Levin, Vladimir; Lichtenberg, Jakob; McGarvey, Con; Ondrusek, Bohus; Rajamani, Sriram; Cook, Byron; Ustuner, Abdullah; Ball, Thomas (EuroSys 2006, 2006)
Bugs in kernel-level device drivers cause 85% of the system crashes in the Windows XP operating system [44]. One of the sources of these errors is the complexity of the Windows driver API itself: programmers must master a complex set of rules about how to use the driver API in order to create drivers that are good clients of the kernel. We have built a static analysis engine that finds API usage errors in C programs. The Static Driver Verifier tool (SDV) uses this engine to find kernel API usage errors in a driver. SDV includes models of the OS and the environment of the device driver, and over sixty API usage rules. SDV is intended to be used by driver developers “out of the box.” Thus, it has stringent requirements: (1) complete automation with no input from the user; (2) a low rate of false errors. We discuss the techniques used in SDV to meet these requirements, and empirical results from running SDV on over one hundred Windows device drivers.